CCTV as an efficient surveillance system? An assessment from 24 academic libraries of India. Issue 4 (16th October 2020) - Gupta, Parul; Margam, Madhusudhan
Abstract : Purpose: The purpose of this paper is to explore the potential and adoption of closed-circuit television (CCTV) surveillance-based security system (hereafter "CCTV") for enhancing the security of library materials in academic libraries of universities (central, state, deemed and private) and prestigious institutions such as Indian Institutes of Technology and Indian Institutes of Management in a developing country, i.e. India. The study also overviewed the CCTV policies of the studied libraries of universities/institutions as they relate to the ethical aspects of the surveillance system. Design/methodology/approach: Structured questionnaire was designed and distributed among librarians of 24 academic libraries covering each zone of India in October 2019 in both physical and online manner. All 24 filled-in questionnaires were collected personally and online by the investigator were found valid eliciting a response rate of 100%. All the 24 filled-in questionnaires were included in the analysis of the interpretation of data. The response to 18 questions was analyzed in the form of tables and figures using descriptive statistical methods. Findings: The study reveals that librarians' found CCTV useful for security by controlling theft, unethical losses and missing items. It also helped to curb mutilation and vandalism, procurement of the rare material via the latest camera devices and night vision capturing, besides improving the service efficiency of the patron, as well as staff. The quantitative study surveyed security professionals to assess how each university/institution developed, deployed and integrated CCTV policies related to securing video data, safeguarding privacy and prevention of the potential for the unethical use of surveillance cameras. The analysis of the survey responses determined that more than 50% of the universities/institutions participating had a written CCTV policy. Further, library professionals find that the future of libraries lies in a CCTV system, so the cost should be brought down to improve return on investment by the mass adoption of this technology in a developing country such as India. Research limitations/implications: The findings of the study showed that the potential uses of CCTV in Indian libraries are slow compared to that of the libraries of developed countries and some of the developing countries. Many of the CCTV policies that universities/institutions did have failed to include mandated training of personnel or provisions ensuring that their policies remained up-to-date. It is suggested that universities and institutions understudy should realize the benefits of CCTV systems and incorporate-related updated tools in the security and multi-purpose uses in the libraries to enhance the services for the users and security for the materials or collections. Practical implications: The paper includes implications for libraries and their professionals to approach CCTV systems with ethical considerations for procurement of library collections, which help to detect mutilation/theft, observe the misbehavior of users, as well as staff and deployment, should not be decided merely while balancing security demands. Social implications: The study is significant because it represents one of the earliest works to shed light on the current level of the use of CCTV system by librarians of studied libraries of universities/institutes in developing country such as India and how they are providing CCTV-based security and services, which are currently in its primitive nature. The study also suggested that select libraries are required to weigh up and balance many competing desires, demands and objectives. Originality/value: This paper provides a concise overview of the various applications/area and uses of CCTV system including its procedures during implementation, merits and demerits while using the system described above in libraries and recommends this technology to other libraries for faster and better services for their users and security to their library materials in today's technological advancement. It provides a set of issues that should be considered before system adoption or deployment.